The impacts of exposure to bisphenol A in the adult female prostate Meriones unguiculatus - Bedolo, Carolina Marques [UNESP] (2023)
The female prostate is associated with the urogenital system and presents homology in morphological terms with the male prostate. Due to its responsiveness to endogenous hormones, this gland is under a constant risk of developing prostatic pathologies and neoplasia when exposed to certain exogenous compounds. Bisphenol A (BPA) is an endocrine disruptor found in different plastic and resin products. Studies have emphasized the effects of perinatal exposure to this compound on different hormone-responsive organs. However, there have been few studies highlighting the influence on female prostate morphology of perinatal exposure to BPA. The objective of this study was to describe the histopathological alterations caused by perinatal exposure to BPA (50 µg/kg) and 17-β estradiol (E2) (35 µg/kg) in the prostate of adult female gerbils. The results showed that E2 and BPA induced proliferative lesions in the female prostate and acted along similar pathways by modulating steroid receptors in the epithelium. BPA was also found to be a pro-inflammatory and pro-angiogenic agent. The impacts of both agents were marked in the prostatic stroma. An increase in the thickness of the smooth muscle layer and a decrease in AR expression were observed, but no alterations in the expression of ERα and ERβ, leading to estrogenic sensitivity of the prostate. However, a peculiar response of the female prostate was to diminish the collagen frequency under BPA exposure correlated to smooth muscle layer. These data therefore indicate the development of features related to estrogenic and non-estrogenic tissue repercussions by BPA perinatally exposure in gerbil female prostate.